THE INFLUENCE OF BRAND IMAGE, DISCOUNT PRICE AND SERVICE QUALITY ON PURCHASE DECISIONS AT J.CO DONUTS & COFFEE PEKANBARU - Endang Sutrisna endang; Ega Minata Praynita Ega; mandataris manda (Journal of Agri Socio Economics and Business, 2023)
This research's context is that a key component of the product marketing concept is to satisfy consumers' requirements and desires while making product choices. A few of the elements that influence consumer purchase decisions include the capacity to develop a brand image among consumers, proper discounts, and service quality. From the analysis of consumer needs and desires, J.CO Donuts & Coffee makes Brand Image, Discounts and Service Quality as part of a marketing strategy to reach consumers. The goal is to ascertain how brand image, discounts, and service quality affect customers' decisions to buy at J.CO Donuts & Coffee Pekanbaru. The research's methodology is quantitative descriptive, and its primary and secondary data sources are J.CO Donuts & Kopi Pekanbaru product sales data from 2016 to 2020, as well as primary data collected through interviews and the distribution of questionnaires, which are then statistically tested using the SPSS program. The analytical methods employed in this study were reliability and validity checks. According to the findings of this study, Brand Image (X1) and Discounts (X2) both had a favorable and significant impact on purchase decisions (Y). Purchase Decision (Y) is positively and significantly impacted by Service Quality (X3).